Development and optimization of fibre reinforced geopolymer concrete using manufactured sand - Ramujee, Kolli; Reddy, K. Adithya; Raju, M. Potha (Journal of Structural Engineering, 2024)
Demand for natural sand and Ordinary Portland Cement(OPC) in the construction industry has consequently increased resulting in the reduction of naturally available sources and an increase in price. In such a situation manufacture sand(M-sand) can be an economical alternative to the river sand and fly ash has proved to be potential alternative to the OPC. In this paper an experimental study has been carried out to investigate the use of M-sand as 100% replacement to fine aggregate and fly ash as 100% replacement to cement in concrete. Sodium hydroxide and sodium silicate solution are used as alkaline activators. Mean while super plasticizer and extra water were added to get desired workability.The ratio of Na₂SiO₃ to NaOH of 2.5 was adopted throughout the work. In the present investigation, the experimental program has been carried out to optimize the parameters influencing the development of fibre reinforced geopolymer concrete. The factors that influence the compressive strength such as percentage of mass of coarse aggregate, size of coarse aggregate, alkaline liquids to fly ash ratio, percentage of super plasticizer, concentration of NaOH(Molarity), curing temperature, curing time, rest period prior to curing, fibre content have been studied. The mix proportion for geopolymer concrete was designed using rigorous trial and error method. The compressive strength and workability are the two indices which forms the basis for optimizing the parameters. The short-term Engineering properties of hardened geopolymer concrete like compressive strength, split tensile strength and flexural strength were examined at 7, 28 days. The results shows that the there is an increase in split tensile strength and flexural strengths of Geopolymer concrete with fibers was observed compared to Geopolymer concrete(GPC) without fibers where as there is no significant enhancement in compressive strength. This shows that the Geopolymer concrete behaves similar to OPC concrete.